EFL teaching-learning approach used for a minimally speaking autistic student at Rosal de los Niños elementary school. - Campaña Mora, Melanie Morelia (2023)
The main objective of this work looks into identifying the elements that may constrain the EFL teaching-learning process used for a minimally speaking student with autism at a preschool in the city of Guayaquil. To achieve this, it was used an action research and mixed method. It was necessary to measure the recognition of the English vocabulary being taught to the student in an inclusive EFL classroom. Additionally, it was applied a teacher observation checklist in order to gather the methodology, techniques and strategies being used by the EFL teacher. The student with autism, and peers were observed to describe their social interaction in the classroom. It was proposed a training course for the teaching staff about the importance of using the TPR Approach and applying hands-on active strategies in the English sessions in an inclusive environment during the scholastic year where the student with autism will be engaged in learning.